Epidemiology and risk factors of preeclampsia; an overview of observational studies - Uzma Shamsi; Sarah Saleem; Noureen Nishter (Al Ameen Medical College, 2013)
Objective: To identify and compile a list of important epidemiological risk factors of preeclampsia among pregnant women from observational studies. Methods: Review of published case control and cohort studies on risk factors of Preeclampsia (PE) by literature search from 1976 -2010 was conducted. 108 studies were selected using search engines of PubMed and Google Scholar. Findings: Most of the studies were case control studies. The factors identified most often were women with a previous history of preeclampsia, pre-existing diabetes, multiple (twin) pregnancy, nulliparity, family history , raised blood pressure (diastolic ≥ 80 mm Hg) at booking, raised body mass index before pregnancy, or increasing maternal age ≥ 40. In some individual studies the risk is also increased with an interval of 10 years or more since a previous pregnancy, autoimmune disease, renal disease and chronic hypertension. Conclusions: These factors and the underlying evidence base can be used to assess risk at booking so that a suitable surveillance routine to detect preeclampsia can be planned for the rest of the pregnancy.